A polygenic risk score for Alzheimer’s disease constructed using APOE-region variants has stronger association than APOE alleles with mild cognitive impairment in Hispanic/Latino adults in the U.S. - Tamar Sofer; Nuzulul Kurniansyah; Einat Granot-Hershkovitz; Matthew O. Goodman; Wassim Tarraf; Iris Broce; Richard B. Lipton; Martha Daviglus; Melissa Lamar; Sylvia Wassertheil-Smoller; Jianwen Cai; Charles S. DeCarli; et al. (Alzheimer’s Research & Therapy, 2023)
Abstract Introduction Polygenic Risk Scores (PRSs) are summaries of genetic risk alleles for an outcome. Methods We used summary statistics from five GWASs of AD to construct PRSs in 4,189 diverse Hispanics/Latinos (mean age 63 years) from the Study of Latinos-Investigation of Neurocognitive Aging (SOL-INCA). We assessed the PRS associations with MCI in the combined set of people and in diverse subgroups, and when including and excluding the APOE gene region. We also assessed PRS associations with MCI in an independent dataset from the Mass General Brigham Biobank. Results A simple sum of 5 PRSs (“PRSsum”), each constructed based on a different AD GWAS, was associated with MCI (OR = 1.28, 95% CI [1.14, 1.41]) in a model adjusted for counts of the APOE- $$ε 2$$ ϵ 2 and APOE- $$ε 4$$ ϵ 4 alleles. Associations of single-GWAS PRSs were weaker. When removing SNPs from the APOE region from the PRSs, the association of PRSsum with MCI was weaker (OR = 1.17, 95% CI [1.04,1.31] with adjustment for APOE alleles). In all association analyses, APOE- $$ε 4$$ ϵ 4 and APOE- $$ε 2$$ ϵ 2 alleles were not associated with MCI. Discussion A sum of AD PRSs is associated with MCI in Hispanic/Latino older adults. Despite no association of APOE- $$ε 4$$ ϵ 4 and APOE- $$ε 2$$ ϵ 2 alleles with MCI, the association of the AD PRS with MCI is stronger when including the APOE region. Thus, APOE variants different than the classic APOE alleles may be important predictors of MCI in Hispanic/Latino adults.